In Europe, Arduous Jobs Fall On First-Generation Migrants. But Later Generations Benefit From Improved Opportunities - Vincent Vandenberghe (Global Labor Organization (GLO), 2025)
This paper contributes to the literature on migrants' labour-market disadvantages by considering one dimension that has received limited attention in Europe: their occupations' (relative) physical arduousness. To quantify their arduousness gap, the paper combines i) data from the European Labour Force Survey (LFS) informing on occupation and immigration status with ii) information on occupational arduousness from the U.S. O*NET database, categorized at the ISCO 3-digit level. The findings reveal that first-generation migrants, particularly women and/or non-EU migrants, are disproportionately concentrated in arduous jobs, experiencing a significant disadvantage in working conditions. However, this disadvantage slowly diminishes over time, with the accumulation of residency in the host country leading to improved occupational outcomes. Notably, second-generation migrants close this gap and even experience a slight advantage in work arduousness compared to native workers, pointing to complete convergence.
Keywords: J81; J62; J71; O15; J24; 330; Work Arduousness; Migrant-Native Arduousness Gap; Working Conditions; Convergence